The war in Iraq - Bodden, Valerie (Turning points (Creative Education, Inc. (Mankato, Minn.)), 2020)
Provides a broad introduction to what led to the war in Iraq, notable events during the war, the response to American aggression and Iraqi distrust, and the consequences of the prolonged engagement. Includes sidebars with notable war stories, a timeline, a glossary, and an index.